Clarifying the charging induced nucleation in glass anode of Li-ion batteries and its enhanced performances. (March 2019) - Zhang, Yanfei; Wang, Peixing; Li, Guangda; Fan, Jiahui; Gao, Chengwei; Wang, Zhaoyang; Yue, Yuanzheng
Abstract: It was recently discovered that nanocrystals could be generated in glass anodes by Li-ion insertion, and thereby the cycling stability of Li-ion batteries was enhanced. Here we reveal the origins of both the nanocrystal formation and the enhancement of battery performances by exploring phase transitions, redox reactions, and structural heterogeneity in glass anodes. We infer that Li + ions interact with the higher energy domains of structural network during discharging/charging, and some of the Li ions are incorporated into the structural network, and thereby the potential energy is lowered through nanocrystal formation. Upon 5000 discharging/charging cycles at a high current density of 1 A g −1, the nanocrystals in the 40TeO2 –60V2 O5 glass were identified to be γ -Li3 VO4 . Owing to the metastable nature of the γ- Li3 VO4 phase, the glass anode becomes electrochemically active and highly ionic conductive. Simultaneously, the cycling stability is greatly enhanced by the nanostructured glass since the nanocrystals could suppress the propagation of micro-cracks generated by volume changes in glass matrix. Graphical abstract: fx1 Highlights: We clarified the Li-insertion induced nucleation in glass anode of Li-ion batteries. Ionic conductivity and cycling stability were enhanced by nanocrystal formation. The nanocrystals in 40TeO2-60V2O5 glass were identified to be γ-Li3VO4 phase. γ-Li3VO4 is a metastable phase benefiting the enhancement of Li-ion conductivity. We explained the origin of the remarkable electrochemical performances.